Peran Rezim 2016 Abu-Dhabi Declaration dalam Usaha Perlindungan Situs Bersejarah di Kawasan Konflik Militer (Studi Kasus : Perancis - Mesir) - Aswin Priyo Baskara; Ika Riswanti Putranti; Muhammad Faizal Alfian (Journal of International Relations Diponegoro, 2022)
ABSTRACT2016 Abu Dhabi Declaration on Safeguarding Endangered Cultural Heritages is a historic site protection regime that focuses on areas of military conflict, especially the Middle East region. Focusing on France and Egypt as representatives of the initiator and participant countries, researchers sought to look at the country's position and response to the declaration, from its formation to post-signing developments to see the impact of the declaration on the issue of protecting historical sites in areas of military conflict, in particular through state analysis. Researchers used qualitative methods with case studies. This research uses literature studies to support the necessary data. Researchers use the international regime theory of Stephen D Krasner. The results showed that the 2016 Abu-Dhabi Declaration met the characteristics of the regime. However, the significance of the declaration has not been able to be seen given its morally binding nature and the limited situation of the relevant state interests and policies that result in the impact on the protection of historic sites has not been able to occur to the fullest. Although not legally binding, the declaration remains a guideline of values on which participating countries' commitments and progress are based on the issue of protecting historic sites in areas of long-term military conflict in the Middle-East Region.Keywords : national interest, role, regime, declaration, military conflict, historical sites